Analisis Miskonsepsi Siswa SMP pada Materi Relasi dan Fungsi Ditinjau dari Gaya Kognitif FI Dan FD - Diah Umi Muzaiyana; Tafsillatul Mufida Asriningsih; Tomy Syafrudin (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2021)
Misconception occurs when a person's conception of material differs from the conception stated by experts in the field. The misconceptions are related to the cognitive style of students. The purpose of this study was to describe the misconceptions experienced by students with Field-Independent (FI) and Field-Dependent (FD) cognitive styles on the topics of relations and functions. This type of research was qualitative research. The research subjects are students of class VIII-I SMPN 1 Jogoroto. Data collection techniques were tests and interviews. The results showed that the misconceptions of FI students were the concept of function, the concept of function in the arrow diagram, and the concept of function graphs and non-function graphs. The misconceptions experienced by FD students were the concept of function, the concept of function in the arrow diagram, the concept of codomain and range, the concepts of function graphs and non-function graphs.